1983
DOI: 10.1002/lsm.1900030111
|View full text |Cite
|
Sign up to set email alerts
|

Is Closure of Open Skin Wounds in Rats Accelerated by Argon Laser Exposure?

Abstract: The influence of linearly polarized argon laser irradiation (lambda = 488 nm and 514.5 nm) on the closure time of standardized open skin wounds was measured in rats. In two separate controlled experiments no acceleration of wound closure by laser irradiation was observed. In the first experiment the wounds were cleaned during the laser treatment period at 1 J/cm2. The second experiment at 4 J/cm2 was without mechanical wound cleaning. The contradictory results reported in the literature and possible influences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

1987
1987
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(10 citation statements)
references
References 8 publications
1
8
0
1
Order By: Relevance
“…In some animal studies low energy laser therapy may have a beneficial effect in wound healing,; however, this has not always been the case,,, Similarly, LELT has been reported to be of help in some human trials, but not others ,. The poor response to LELT may be explained by the lack of optimization of parameters which determine the clinical response, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In some animal studies low energy laser therapy may have a beneficial effect in wound healing,; however, this has not always been the case,,, Similarly, LELT has been reported to be of help in some human trials, but not others ,. The poor response to LELT may be explained by the lack of optimization of parameters which determine the clinical response, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have addressed the potential effects of low energy lasers on wound healing in humans. The results have been somewhat conflicting in that some studies have been able to document enhancement of wound healing 9 while some studies have reported negative results 5,6 . Relevant to this issue is our observation that type III procollagen mRNA level was elevated in laser‐treated wounds, as early as day 10, in a pig wound healing model.…”
Section: Laser Stimulation Of Wound Healing In Vivomentioning
confidence: 94%
“…A considerable amount of conflicting literature exists concerning the effects of low energy lasers on wound healing. Although negative results have been reported, 5,6 several studies suggest enhancement of the wound healing in both experimental animal models, 7,8 and human studies 9 . Since this area of laser biology is potentially important, we have recently initiated extensive studies examining the effects of low energy lasers on fibroblast functions 10 and wound healing in vivo 11,12 .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have indicated the enhancement of wound healing both in animal models and in patients. On the other hand, some of the studies were unable to document the beneficial effects of low-power lasers on wound healing [17,22]. Ikeuchi et al [23] studied the effects of He-Ne laser irradiation on the wound healing ability of guinea pig skin, and it was suggested that low-power laser irradiation accelerated the compositon of type III collagen for wound healing following incisions.…”
Section: Discussionmentioning
confidence: 99%